2024
DOI: 10.1021/jacs.3c14434
|View full text |Cite
|
Sign up to set email alerts
|

Boronic Acid-Catalyzed Regio- and Stereoselective N-Glycosylations of Purines and Other Azole Heterocycles: Access to Nucleoside Analogues

Shrey P. Desai,
Giorgos Yatzoglou,
Julia A. Turner
et al.

Abstract: In the presence of an arylboronic acid catalyst, azole-type heterocycles, including purines, tetrazoles, triazoles, indazoles, and benzo-fused congeners, undergo regio-and stereoselective N-glycosylations with furanosyl and pyranosyl trichloroacetimidate donors. The protocol, which does not require stoichiometric activators, specialized leaving groups, or drying agents, provides access to nucleoside analogues and enables late-stage N-glycosylation of azole-containing pharmaceutical agents. A mechanism involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 102 publications
(76 reference statements)
1
1
0
Order By: Relevance
“…These questions are summarized in Scheme , which also depicts a simplified proposal for the catalytic cycle and an overview of the techniques used in this study. A key intermediate in the proposed cycle is ion pair B ; its involvement would account for the effect of the boronic acid catalyst on regioselectivity in a way that is consistent with the broader mechanistic picture of azole activation via tetracoordinate boron complexes that has emerged from our work . Identifying the turnover frequency-determining transition state and intermediate(s), along with the step responsible for the regioselectivity of azole functionalization, was an important goal for this study.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…These questions are summarized in Scheme , which also depicts a simplified proposal for the catalytic cycle and an overview of the techniques used in this study. A key intermediate in the proposed cycle is ion pair B ; its involvement would account for the effect of the boronic acid catalyst on regioselectivity in a way that is consistent with the broader mechanistic picture of azole activation via tetracoordinate boron complexes that has emerged from our work . Identifying the turnover frequency-determining transition state and intermediate(s), along with the step responsible for the regioselectivity of azole functionalization, was an important goal for this study.…”
Section: Introductionsupporting
confidence: 65%
“…Numerous approaches for the regioselective N-functionalization of azoles have been developed over the years, including diverse catalytic methods. Using catalysis to access otherwise elusive substitution patterns and the development of protocols that are broadly applicable across the numerous heterocycle types that fall into this structural class are among the directions of ongoing research. Our group has shown that organoboron catalysts (diarylborinic acids and arylboronic acids) activate pyrazoles, triazoles, tetrazoles, benzotriazoles, and purines toward regioselective N-functionalization reactions with diverse electrophilic reaction partners . The proposed mechanism of activation involves the formation of a tetracoordinate organoboron–azole complex that displays enhanced nucleophilicity.…”
Section: Introductionmentioning
confidence: 99%